Міфи позитивного права та сучасна правова традиція - Завальнюк, Володимир Васильович; Завальнюк, Владимир Васильевич; Zavalniuk, V. (My University, 2011)
Equality of man and society or humanity as a whole means that person by virtue of its spirituality is an individual embodiment of the total; that is why all of humanity remains rightless even if there is only one of its representative. So let to start solving metaproblem of law not from law in sociology and anthropology of law. The study of law should start with research mikrojurisprudence as the genesis of the inherent rights, analysis of its origins, causes and conditions of its emergence and development.
Завальнюк В. В. Міфи позитивного права та сучасна правова традиція / Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. – Одеса : Фенікс, 2011. – Вип. 42. – С.3-12.
Keywords: Правова традиція; Правоведення; Міфи права; Мифы права; Правоведение; Правовая традицыя; Legal traditsyya; jurisprudence; Myths rights